2007
DOI: 10.1164/rccm.200703-489oc
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Impact of Bronchiectasis in α1-Antitrypsin Deficiency

Abstract: Emphysema is the predominant component of COPD in AAT deficiency, but the prevalence and impact of airway disease are greater than currently recognized. Consequently, future therapeutic strategies in AAT deficiency should also target this component of COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
127
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(144 citation statements)
references
References 37 publications
6
127
0
4
Order By: Relevance
“…Our data would contradict these findings, demonstrating that radiologically detected bronchiectasis is both common in AATD and that there is no dependent relationship to emphysema or indeed a history of smoking. This is supported by similar studies on bronchiectasis and emphysema in AATD and also by registry data showing a high prevalence of bronchiectasis in the AATD population in Spain and Italy (14,23). Most people in our study had evidence of mild radiological bronchiectasis with minimal associated clinical symptoms such as increased frequency of cough or pulmonary exacerbation compared to those with emphysema, however those with more severe bronchiectasis did report significantly poorer health status outcomes.…”
Section: Discussionsupporting
confidence: 88%
“…Our data would contradict these findings, demonstrating that radiologically detected bronchiectasis is both common in AATD and that there is no dependent relationship to emphysema or indeed a history of smoking. This is supported by similar studies on bronchiectasis and emphysema in AATD and also by registry data showing a high prevalence of bronchiectasis in the AATD population in Spain and Italy (14,23). Most people in our study had evidence of mild radiological bronchiectasis with minimal associated clinical symptoms such as increased frequency of cough or pulmonary exacerbation compared to those with emphysema, however those with more severe bronchiectasis did report significantly poorer health status outcomes.…”
Section: Discussionsupporting
confidence: 88%
“…Although there is substantial evidence that the presence of bronchiectasis is common in patients with severe AAT deficiency, (11) the genesis of bronchiectasis is certainly multifactorial.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that patients with COPD and comorbid bronchiectasis have higher risk of becoming chronic sputum producers, have more purulent sputum, have more airway or systemic inflammation, and have more exacerbations. [1][2][3][7][8][9][10] The worse clinical outcomes in patients with COPD and comorbid bronchiectasis may be associated with chronic colonization of potentially pathogenic microorganisms (PPMs). In earlier studies, PPMs were isolated more frequently from the sputum of patients with COPD and comorbid bronchiectasis during the stable phase, 7,9 as well as during acute exacerbation.…”
Section: Ni Et Almentioning
confidence: 99%